Assessing the influence of heat treatments on γ-TiAl joints - Guedes, A. (2006)
The heat treatment of γ-TiAl alloy (Ti-47Al-2Cr-2Nb (at.%)) diffusion brazed joints was investigated. Joining was performed using a Ti/Ni/Ti clad-laminated braze alloy foil at 1050 and 1150ºC with a dwell time of 10 minutes. The joints were subsequently heat treated at 1250 and 1350ºC for 240 and 30 minutes, respectively. The microstructure and the chemical composition of the interfaces were analysed by scanning electron microscopy (SEM) and by energy dispersive X-ray spectroscopy (EDS), respectively. Microhardness tests performed across the interface were used to roughly predict the mechanical behaviour of the as-diffusion brazed and of the heat treated joints. Diffusion brazing produced interfaces with two distinct layers essentially composed of α2-Ti3Al and of TiNiAl; γ-TiAl was also detected for joining at 1150ºC. After heat treating, the as-diffusion brazed microstructure of the interface was completely replaced by a mixture essentially composed of γ-TiAl and α2–Ti3Al single phase grains and of (α2 + γ) lamellar grains. Microhardness tests showed that the hardness of the as-diffusion brazed interfaces, which ranges from 567 to 844 HV (15 gf), is significantly higher than that of the titanium aluminide alloy (272 HV). All post-joining heat treatments lowered substantially the hardness of the interface, as the hardness of the main phases detected at the interfacial zone after heat treating the joints is comprised between 296 and 414 HV.